HOT COMPRESSION TEST OF 9 Cr-1 Mo STEEL – NUMERICAL SIMULATION - Alica Fedoriková (Acta Metallurgica Slovaca, 2016)
This paper is focused on the evaluation of formability of heat resistant steel type 9Cr-1Mo by laboratory numerical simulation – hot compression test confirmed by laboratory hot compression test. The 9Cr-1Mo steel represents modern 9%Cr tempered martensitic steel for high temperature applications in advanced thermal power plants. Numerical simulations were computed in software Deform 3D for five proposed sample shapes. On the base of normalized Cockcroft-Latham criterion (nCL), indicating the material damage during deformation, the sample type “tapered roller with four axial notches” was found to be the most suitable for hot workability evaluation. On base of simulations, it is also evaluated the temperature range of the workability of 9Cr-1Mo. The interval of good workability according to the nCL criteria is in the temperature range from 650 to 950 °C.